Galunisertib attenuates pulmonary fibrosis with silicosis in mouse via TGF-β/TRAF6/Beclin1 signaling pathway - Li, Rou; Kang, Huimin; Hu, Aoxiang; Chen, Guo; Yan, Tinghua; Liu, Ting; Chen, Shi (Frontiers in Pharmacology, 2025)
ObjectiveSilicosis is characterized by silicon nodules and diffuse pulmonary fibrosis. To date, no effective therapy has been developed for the treatment of silicosis. This study aimed to investigate the effects of Galunisertib, a TGF-β receptor I kinase inhibitor, on the autophagy-lysosome system and pulmonary fibrosis in a SiO2-induced silicotic mouse model and cells.MethodsWe established a silica-induced pulmonary fibrosis mouse and cell model. The MTT assay was used to determine the processing time and dose of cell experiments. Cell scratch assays were used to explore the effect of Galunisertib on the proliferation and migration ability of silica-stimulated fibroblasts. Cell migration was evaluated through wound healing, and the interactions between TGF-β and TRAF6/Beclin1 were verified by molecular docking and co-immunoprecipitation (Co-IP). WB and qPCR were used to detect the protein and transcription levels of TGF-β, Col-I, and α-SMA in each group, as well as the expression levels of autophagy-related protein LC3II/I, autophagy substrate protein p62, lysosome-associated membrane protein LAMP2, and pathway-related proteins TGF-β, TRAF6, and Beclin1. WB was also used to detect the expression level of apoptosis-related protein Cleaved-caspase 3 in the lung tissues and cells of mice in each group.ResultsWe found that Galunisertib has good anti-fibrosis activity both in vitro and in vivo. A 4-week Galunisertib treatment markedly ameliorated inflammation and fibrosis. Moreover, the results revealed that Galunisertib inhibited the expression of TGF-β, downregulated the major fibrotic protein expression of collagen I and a-smooth muscle actin (α-SMA), thereby switching the progression of fibroblast-to-myofibroblast transition (FMT). Furthermore, Evidence from Co-IP and molecular docking assays confirmed that this inhibition also involves the suppression of TRAF6 and Beclin1. Therefore, Galunisertib administration significantly altered the protein levels of LC3 and p62, implying that the autophagy-lysosome system might be involved in pulmonary fibrosis.ConclusionThese findings indicate that Galunisertib can modulate autophagy in pulmonary tissues of silicotic mice and fibroblast cells by suppressing the TGF-β/TRAF6/Beclin1 signaling pathway. On the other hand, Galunisertib regulates autophagy and inhibits the activation, proliferation and migration of Silica-stimulated fibroblasts, alleviating fibrosis in silicosis mice. Altogether, Galunisertib may be a potential candidate drug for preventing pulmonary fibrosis.